Association Between Deviated Nasal Septum and Function of Eustachian Tube among Patients Attending a Tertiary Care Center - Shrestha, Kundan Kumar; Dhungana, Anup; Rijal, Anupama Shah; Joshi, Rupesh Raj; Shrestha, Shivani; Karki, Srijana (Nepal Medical College Journal, 2024)
Deviated nasal septum is the most common cause of severe and chronic nose blockage. The eustachian tube (ET) is a tube that connects the middle ear cavity and the nasopharynx and provides middle ear ventilation. The relationship between DNS and ETF is controversial in medical literature. This study tried to find the association between deviated nasal septum and function of eustachian tube. This prospective study was conducted in Nepal Medical College Teaching Hospital, Otorhinolarynology Department from November 2022 to October2023 after acquiring ethical clearance from Institutional Review Committee. All the patients presenting to the outpatient clinic over the age of 19 with deviated nasal septum (DNS) were included. Statistical analysis was done using SPSS. A p value of < 0.05 was considered statistically significant. Our study had 71 males (54.6%) and 59 females (45.4%) with mean age 37.2±15.9 years. Of 130 patients, 56 (43.1%) had DNS to right side while 74 (56.9%) to left. All patients had moderate DNS. Age group, gender, and laterality of DNS of the patient did not show any significant association with ETDQ7 score, tympanograms and middle ear pressures on either side. Moderate DNS did not affect ETF in a significant way.